Family management and firm performance in family SMEs: the mediating roles of management control systems and technological innovation - Ruiz-Palomo, Daniel (2019)
The aim of this research is to analyze the mediating role of the use of management control systems (MCS) and the achievement of technological innovation (TI) in the relationship between family management and firm performance in family small and medium-sized enterprises (SMEs). A questionnaire was conducted by 617 managers of family SMEs in Spain, and our model was tested using partial least squares. Our findings show that both MCS and TI play crucial mediating roles in the understanding of the relationship between family management and firm performance. As a result, family-managed firms that utilize MCS and produce TI are much more likely to generate better performance. These results encourage family managers to use formal MCS because in that way they will contribute to obtaining better firm performance, directly and indirectly through TI. We focus on private family SMEs, because these specific firms contribute significantly to the economies worldwide. This paper contributes to resolve the controversy regarding the relationship between family management and firm performance introducing MCS and TI as mediating factors.